Application of the Agile Methods in Jesus' Teachings About “the Church”: (Based on the Gospel of John) - Pap, Yonas; Sitepu, Edward; Isriyanto, Isriyanto; Sembiring, Milisi; Ndruru, Sokhitohugo; Budiyanto, Joko (Technium Education and Humanities, 2025)
The use of agile methods in the field of theology is still unexplored. Especially because the world of work is considered different from theology. This article seeks the discovery and contribution of agile methods to the teachings of Jesus. The content of Jesus' teachings about the church in the Gospel of John is the focus of this study. Using the characterization of the text and the priority of the text, three important variables are obtained as factors that confirm Jesus' teachings about the church. The findings show the highest score in the cognitive aspect of believers/churches, then the aspect of the unity of God's people and finally behavior change. This is done using loading factor analysis.